Isolation , Partial Characterization of a Flavone From Sudanese Terminalia brownii (Comretaceae) Root and Biological Activity of Ethanol Extract - Karim, Mohamed Abdel; Ibrahim, M ,; Mohamed,S.,; Ayda,Y, (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2019)
Terminalia brownii is widely used in African system of medicine as a natural remedy for cough, tonsillitis, typhoid, tooth-ache, snake bite and rheumatic pain . Phytochemical screening of Terminalia brownii root revealed the presence of flavonoids , alkaloids,steroids, tannins, terpenes, saponins and coumarins. A flavonoid - compound I- was isolated from the ethanol extract by  paper chromatography and its structure was partially characterized via some spectral data ( UV and 1HNMR).In the agar diffusion bioassay,the ethanol extract showed significant activity against Pseudomonas aeruginosa and Staphylococcus aureus. It  exhibited moderate activity against Escherichia coli and the yeast Candida albicans . It also showed moderate free radical scavenging capacity  against stable DPPH radicals.